CAR-T cell Therapy; Toxicities and Current aspects of Management - Tiwari, Bishal; Sapkota, Samita; Afshan, Roshan (Nepalese Journal of Cancer, 2025)
Chimeric antigen receptor (CAR) T cell therapy has redefined the treatment paradigm for hematological malignancies, offering remarkable remission rates and survival benefits. However, its clinical application is hampered by severe toxicities, notably cytokine release syndrome (CRS) and immune effector cellassociated neurotoxicity syndrome (ICANS), which pose significant management challenges. This review critically evaluates current toxicity profiles, elucidates underlying pathophysiological mechanisms, and assesses contemporary management strategies—including supportive care, corticosteroids, and cytokine inhibitors such as tocilizumab. Furthermore, we explore innovative approaches like dual CAR constructs, armored CAR-T cells, tonic signaling modulation, and the incorporation of suicide genes that promise to mitigate adverse effects while preserving therapeutic efficacy. By integrating emerging clinical evidence and novel therapeutic concepts, our analysis aims to inform future research directions and optimize patient outcomes in the evolving landscape of CAR T cell therapy.